Consequences of Aid Volatility for Macroeconomic Management and Aid Effectiveness. (May 2015) - Hudson, John
Highlights: The most volatile aid sectors per se include debt, industry, and humanitarian aid. The least volatile aid sectors per se include education and health. Sector specific aid volatility is often corrected for in the following period. We examine the impact of aid and aid volatility on school completion and death rates. We examine the impact of aid and aid volatility on Internet and mobile phones usage. Summary: We conclude that individual aid sector volatility matters as well as total aid volatility. Easily, the most important contributor to total volatility is debt aid. The most volatile aid sectors per se include debt, industry, and humanitarian, and the least include education and health. In several sectors volatility appears to have peaked around 2006. Within individual countries, sector volatility is often corrected for in the following period, there are also sometimes knock-on effects on other sectors. Finally we examine the impact of sector aid, and aid volatility, on school completion rates, death rates, Internet usage, and mobile phone subscriptions.